Persian and Arabic Calendars as Presented by Anania Shirkatsi - Broutian, Grigor (ՀՀ ԳԱԱ)
Here is an attempt to present the ideas concerning the Medieval Persian and Arabic calendars as offered in the works of the 7th century A.D. Armenian scientist Anania Shirakatsi. The calendars of Christian Persians and Arabs, as explained in Anania’s work, are of the Julian type, with 365.25 days per year. By Persian and Arabic Calendars, he means variants of the Julian calendar used by groups of Christians living in the Persian and Arabic lands. These calendars had a structure very different from what is generally known as Arabic or Islamic and the traditional Persian calendar.
Keywords: History